Prevalence of sub superior bronchus. A bronchoscopic study - Thakur, Binay; Khatiwada, Sagar; Tiwari, Manoj; Bhattarai, Shachee; Thapa, Shrijana; Kharel, Ashish; Adhikari, Mahesh Mani (Nepalese Journal of Cancer, 2025)
Background: The sub superior bronchus (B*) is an atypical/ accessory bronchus in lower lobe. With the global increase in indication of segmentectomy especially for lung cancer, it has received higher attention from thoracic surgeons. The aim of our study was to properly identify B* during bronchoscopy and elucidate its prevalence. Methods: A thorough examination of bronchial tree was done during bronchoscopy in 60 patients. The indications were mostly for suspected malignancy. All the segmental bronchi (B1-10) were properly identified. Any accessory bronchus in lower lobar bronchus below B6 was labelled as B* and a video/ photo was captured for discussion among the investigators. Results: B* was identified in 31.6% cases with an incidence of 21.6% in right side and 10% in left side. B6, (B7), B8, B9+10 configuration was found to be associated mostly with the presence of B* in right side (p=.005) whereas B* was exclusively associated with that configuration in left side (p<.001). Conclusion: Proper identification of B* can be done by bronchoscopy and its prevalence (31.6%) is not uncommon.